Two new species of Actinote (Lepidoptera, Nymphalidae) from Southeastern Brazil - Francini, Ronaldo Bastos; Freitas, André Victor Lucci; Penz, Carla (Zootaxa, 2004)
Two new species of Actinote (Nymphalidae, Heliconiinae, Acraeini) are described from southeastern Brazil. Actinote eberti sp. nov. occurs in the Serra da Mantiqueira region and resembles members of the Actinote black-yellow mimicry group. Actinote pratensis sp. nov. is found in widely scattered points in the rich-soil central S o Paulo transition between montane and semideciduous atlantic forest, and belongs to the orange-yellow mimicry group.